Mobilisation of trace elements on roofing tiles. Issue 2 (April 2016) - Sulaiman, Fazrul Razman; Brimblecombe, Peter; Grossi, Carlota M.
Roofs surfaces are frequently used to catch water for drinking in many countries, so the presence and mobilisation of material into runoff water can be an important process to consider. This paper investigates the origin and mobilisation of trace elements from roofing tiles. Our work suggests that trace elements can mobilise into roof runoff. However, lead by contrast, appears to have accumulated at the surface of tiles exposed to busy automobile traffic that used leaded fuel (confirmed by X-ray fluorescence). Although lead is relatively immobile on the tile surface, the potential for leaching by acidic rain (pH < 4) means that the guidelines for lead in drinking water may be exceeded during some rainfall events.